THE CULTURAL WISDOM AS FOUNDATION FOR CHARACTER DEVELOPMENT APPROACH - W, Hernawati; Wiratih, Retno (Jurnal Pendidikan Karakter, 2011)
Abstract: Culturally, wisdom is the basis for the integration of cognitive and affective domains that show the qualities of personality. Culture is the bridge between health and psychology (mentality). Health comes from the word wholeness, to be complete. Wise men live their daily lives in accordance with wisw perspectives and wise values. Culture and wisdom help us reach our wholeness by illuminating our inner world with the wisdom of our ancestors, and help, and help us discover our talents. The wholeness within the individual and the wholeness and relations with the nature are the essentials of character development, that sooner or later will create harmony. Our tradition as ancient rattle keepers contains the best seeds of the harvest for whatever reason. In community building our life is enhanced. We are constantly growing as persons. Our life has meaning. You can see how their lives are better because you are part of them. You have a place in their circle of life. Their actions make the world around them a better place to grow. They resolve conflicts and in other ways maximize harmony and general well-being. They live compassionately. Community construct is constantly taking place between themselves and the universe, and what needs to be done. The point is they see themselves and the rest of humanity as being itself in evolving and living with values. Key words: culture, wisdom, person, self, community